Who shapes the CJEU regulatory jurisprudence? On the epistemic power of economic actors and ways to counter it. Issue 3 (September 2022) - Morvillo, Marta; Weimer, Maria
Abstract: What role does the Court of Justice of the European Union (CJEU) play in holding European Union (EU) regulatory science, ie the science underpinning public regulation, to account for its epistemic quality? Since Pfizer, CJEU case law has strengthened the role of science in both EU risk regulation and litigation, whilst intensifying judicial scrutiny of scientific reasoning based on procedural standards. Scholars often welcome this approach as striking an adequate balance between effective judicial protection and institutional competence. Some praise the Court as an 'information catalyst' promoting procedures, in which epistemic quality is ensured through diligent consideration of and deliberation among all relevant voices. These debates, however, overlook the role of economic actors as information providers, in and challengers of EU risk regulation. This paper re-evaluates the modern post- Pfizer approach from a new, socio-legal perspective by studying, for the first time, the interactions between judicial review and the epistemic power of economic actors, ie their relative ability to influence what EU regulators know at the expense of other actors. We combine an epistemologically informed comparative institutional analysis with doctrinal critique of CJEU case law. Our findings show the need to rethink both legal standing and procedural review in EU risk regulation. Instead of catalysing inclusive procedures that open regulatory science to public scrutiny, the modern approach fosters an exclusive bilateral information exchange between the administration and the regulated industry. The Court reduces the function of process values, such as duty of care and reason-giving, to the protection of a small circle of actors, neglecting the public interest dimension of such values. Thus, the modern approach fails to address, and instead further entrenches the epistemic power imbalances inherent in EU risk regulation. We end by sketching out a normative and doctrinally sound vision of how CJEU review could contribute to EU expert accountability in a more publicly oriented way.